1984
DOI: 10.1007/bf00502449
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of cerebral noradrenaline turnover after morphine withdrawal and its retardation by acute morphine administration in rats

Abstract: To clarify the effects of withdrawal from chronic morphine treatment on cerebral noradrenaline (NA) turnover, we have measured the alpha-methyl-p-tyrosine (alpha MT)-induced depletion of NA in five brain areas of male Wistar rats given morphine twice daily for 40 or 60 days. After the last morphine dose (50 or 70 mg/kg) the rats were withdrawn for 1, 2 or 4 days. In order to study the development of tolerance a challenge dose of 10 mg/kg of morphine was given to some of the rats. Withdrawal of morphine acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…In mice acute morphine accelerates noradrenaline (NA) turnover in all brain areas and tolerance develops towards these effects (Smith et al 1970(Smith et al & 1972Rosenman & Smith 1972;Bloom et al 1976;Kempf et al 1976;Attila et al 1987;Etemadzadeh 1993). In rats acute morphine elevates sulphated 3-methoxy-4-hydroxyphenylethylene glycol (MO-PEG) concentration in all brain areas as well as enhances the a-methyl-p-tyrosine (aMT)-induced NA depletion in the lower brain stem but retards it in the cortical areas; however, tolerance develops only to the NA turnover enhancing effects of acute morphine (Roffman et al 1977;Attila & Ahtee 1983Ahtee et al 1989;Attila 1989). While Author for correspondence: Liisa Ahtee, Division of Pharmacology and Toxicology, Department of Pharmacy, PO.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In mice acute morphine accelerates noradrenaline (NA) turnover in all brain areas and tolerance develops towards these effects (Smith et al 1970(Smith et al & 1972Rosenman & Smith 1972;Bloom et al 1976;Kempf et al 1976;Attila et al 1987;Etemadzadeh 1993). In rats acute morphine elevates sulphated 3-methoxy-4-hydroxyphenylethylene glycol (MO-PEG) concentration in all brain areas as well as enhances the a-methyl-p-tyrosine (aMT)-induced NA depletion in the lower brain stem but retards it in the cortical areas; however, tolerance develops only to the NA turnover enhancing effects of acute morphine (Roffman et al 1977;Attila & Ahtee 1983Ahtee et al 1989;Attila 1989). While Author for correspondence: Liisa Ahtee, Division of Pharmacology and Toxicology, Department of Pharmacy, PO.…”
mentioning
confidence: 99%
“…Morphine withdrawal clearly increases cerebral NA turnover and release in rats (Gunne et al 1969;Gramsch & Blasig 1976;Crawley et al 1979;Swann et al 1983;Attila & Ahtee 1983Ahtee et al 1989) but in mice the reports are few and the results controversial: no increase of the cortical free MOPEG concentration (Funada et al 1993), increase of the aMT-induced NA depletion only in some brain nuclei (Kovacs et al 1983) or even retardation of NA synthesis rate in the whole brain (Rosenman & Smith 1972;Smith et al 1972). Futher, there is no thorough study about the effects of morphine withdrawal and challenge on free MOPEG, the main metabolite of NA and thus a functional index of NA turnover in the mouse brain (Sharman 1969;Ceasar et al 1974;Heal et al 1989).…”
mentioning
confidence: 99%
“…In rat brain morphine enhances the aMT-induced depletion of NA and elevates the concentration of 3-methoxy-4-hydroxyphenylglycol only in large doses and not in all brain areas (Gunne et al 1969;Sugrue 1974;Papeschi et al 1975;Paalzow & Paalzow 1975;Gomes et al 1976;Roffman et al 1977;Dettmar et al 1981;Tanaka et al 1983). Furthermore, we found that morphine clearly retarded the aMT-induced NA depletion in the cortical hemispheres of rats (Attila et al 1981;Attila & Ahtee 1983& 1984a. Several investigators found that morphine increases NA turnover in mouse whole brain (Smith et al 1972;Bloom et al 1976;Cott & Engel 1977).…”
mentioning
confidence: 73%
“…The method described by Keller et al (1976) was slightly modified. For details see Attila & Ahtee (1984a). One-way ANOVA followed by Student's t-test (pooled variance) was used when comparing the means of morphine-treated and aMT-treated mice.…”
Section: Methodsmentioning
confidence: 99%
“…Central catecholaminergic neuronal systems have been implicated in opiate dependence and withdrawal in many studies (for review see Redmond & Krystal 1984). However, the effects of opiate withdrawal on the central nervous system are complex and regional differences in brain noradrenaline (NA) turnover after morphine withdrawal have been found (Attila & Ahtee 1984). The relation-ship between central catecholaminergic neuronal systems in opiate withdrawal and the peripheral sympathetic nervous system is not clear.…”
Section: Introductionmentioning
confidence: 99%